Handbook of research on cyber security intelligence and analytics - Kumar, S P. Pavan; Pooja, M. R.; Gururaj, H. L.; Jena, Om Prakash (IGI Global, 2022)
"This book looks at the intersection of Artificial Intelligence and Cyber security which has emerged as one of the most promising use cases for the advancement of Cyber security in the technological age.